THE PROBLEM OF LANGUAGE LEARNING AND NATIONAL LANGUAGE VALUE IN MAHMUDKHOJA BEHBUDI JOURNALISM (Scientific journal of the Fergana State University, 2024)
The article analyzes articles by Mahmudhodji Behbudi, a prominent representative of modern artists of Turkestan, on the problem of studying foreign languages, the national language, which is a symbol of the nation, and its place in the life of the country. , its cushioning and its protection.